Dipole modeling of multispectral signal for detecting metallic biopsy markers during MRI‐guided breast biopsy: a pilot study. Issue 4 (21st October 2019) - Eskreis‐Winkler, Sarah; Simon, Katherine; Reichman, Melissa; Spincemaille, Pascal; Nguyen, Thanh; Kee, Youngwook; Cho, Junghun; Christos, Paul J.; Drotman, Michele; Prince, Martin R.; Morris, Elizabeth A.; Wang, Yi
Abstract : Purpose: During MRI‐guided breast biopsy, a metallic biopsy marker is deployed at the biopsy site to guide future interventions. Conventional MRI during biopsy cannot distinguish such markers from biopsy site air, and a post‐biopsy mammogram is therefore performed to localize marker placement. The purpose of this pilot study is to develop dipole modeling of multispectral signal (DIMMS) as an MRI alternative to eliminate the cost, inefficiency, inconvenience, and ionizing radiation of a mammogram for biopsy marker localization. Methods: DIMMS detects and localizes the biopsy marker by fitting the measured multispectral imaging (MSI) signal to the MRI signal model and marker properties. MSI was performed on phantoms containing titanium biopsy markers and air to illustrate the clinical challenge that DIMMS addresses and on 20 patients undergoing MRI‐guided breast biopsy to assess DIMMS feasibility for marker detection. DIMMS was compared to conventional MSI field map thresholding, using the post‐procedure mammogram as the reference standard. Results: Biopsy markers were detected and localized in 20 of 20 cases using MSI with automated DIMMS post‐processing (using a threshold of 0.7) and in 18 of 20 cases using MSI field mapping (using a threshold of 0.65 kHz). Conclusion: MSI with DIMMS post‐processing is a feasible technique for biopsy marker detection and localization during MRI‐guided breast biopsy. With a 2‐min MSI scan, DIMMS is a promising MRI alternative to the standard‐of‐care post‐biopsy mammogram.